Analysis of the Residual Stress and Deformation of Spiral Bevel Gear Heat Treatment Process based DEDORM Software Finite Element Simulation - Wang Yanzhong; Chen Yunlong; Zhang Zuzhi; Chen Yanyan; Liu Yang (Jixie chuandong)
Based on the basic principles of heat transfer and thermal elastic- plastic theory,by using finite element method,the heat treatment analytical model of spiral bevel gear is established. The influence of carburizing quenching process on tooth residual stress distribution and deformation is simulated by DEFORM software. The variation law of microstructure,residual stress and tooth deformation with time in the carburizing quenching process are obtained. The influence of different quenching temperature on tooth residual stress,deformation and performance is researched. The simulation results show that the compressive stress on tooth surface and the tensile stress on core portion are formed after heat treatment. The tooth surface residual compressive stress is increased with the quenching temperature. This can improve the fatigue property and performance of spiral bevel gear. The analysis of tooth surface deformation can provide certain theoretical guidance for the subsequent spiral bevel gear grinding process parameter.